O realismo direto na teoria da cognição intelectual de Tomás de Aquino - Gilson Damasceno Linhares (Medievalista)
This text aims at an introductory presentation of the interpretative hypothesis of direct realism, with regard to the relationship between the concept and the object, in Thomasian gnosiology. Direct realism raises the hypothesis that there is a formal identity relationship between the species intelligibilis / concept and the external thing. Due to this thesis of formal identity, we must deny that such entities are intermediaries between the intellect and the thing. Therefore, the denial of an intermediate mental entity would exclude a representationalist interpretation. After analyzing the main theses of direct realism, we intend to propose some objections to these. We will object to the central thesis of formal identity and its basis, namely, the common form.